Foucauldian Discourse Analysis of Bullying Power Dynamics in Higher Education - Essie-Elizabeth Pippins; Esther Pippins (Adult Education Research Conference, 2022)
This study utilizes Foucauldian discourse analysis to examine how tenured faculty members and adjunct instructors experience bullying through language and micro-aggressive behaviors, a particular focus on gender bullying.
Keywords: bullying; micro-aggressive behaviors; higher education; gender; adjunct